An exploration of parental age in relation to parents' psychological health, child adjustment and experiences of being an older parent in families formed through egg donation. Issue 2 (August 2022) - Jadva, Vasanti; Lysons, Joanna; Imrie, Susan; Golombok, Susan
Abstract: Research question: Is parental age associated with parents' psychological health, couple relationship satisfaction and child adjustment in egg donation families, and how do parents think and feel about their age in relation to parenting? Design: Seventy-two families with a child born after IVF egg donation were included. Mothers were aged between 32 and 51 years and fathers between 31 and 61 years when the target child was born. When the child was aged 5 years, parents were interviewed and asked to complete questionnaire assessments of parenting stress, anxiety, depression, marital quality and child adjustment. Results: Older parents experienced more parenting stress and poorer couple relationship quality than younger parents. No differences were found for child adjustment. Qualitative content analysis of the interviews revealed themes related to 'health and mortality', 'giving and receiving support', 'treatment and age', 'positive aspects of older parenting' and 'other'. Conclusions: This exploratory study found that older parents experienced greater parental stress and poorer relationship quality. Some parents had concerns about their older age, specifically in relation to their health and mortality. It would be important to follow up these families as the child grows older to understand the child's thoughts and feelings about having older parents. Furthermore, findings should be replicated in a larger sample of families formed through egg donation, which includes more younger mothers who have used egg donation.